2022
DOI: 10.3390/agriculture12030325
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Phosphorus Fertilizers Derived from Recycled Biogas Digestate as Applied to Maize and Ryegrass in Soils with Different pH

Abstract: Three phosphorus (P) fertilizer fractions recycled from biogas digestates were tested alone and in combination for their efficiency in two agricultural surface soils with different pH: a silty sandy loam and a clay loam. The experiments were carried out in pots under greenhouse conditions, using mineral triple superphosphate (TSP) as a reference. Maize was cultivated for 50 days, followed by ryegrass cultivation for an additional 84 days in the same soil, without additional fertilization. The variables investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In a crop rotation involving forage maize, potatoes (Solanum tuberosum L.), fodder beet (Beta vulgaris L.), and oats (Avena sativa L.), Vanden Nest et al (2015) found that application of solid phase digestate based on a mixture of organic waste, energy crops, and animal slurry increased soil calcium chloride-extractable phosphorus (P-CaCl 2 ) concentration and phosphorus leaching but not soil ammonium lactate-extractable phosphorus (P-AL) concentration, hot water-extractable phosphorus, or crop yield or quality compared with application of equal, higher, or lower doses of TSP to a soil with initially high phosphorus status. Bach et al (2022) found similar or higher maize biomass and biomass phosphorus content in treatments that received phosphorus as struvite, calcium phosphate, and magnesium phosphate precipitated from cow manure and maize silage-based digestate in combination with dried solid phase of the same types of digestate, than in treatments that received phosphorus as TSP on two soils with low phosphorus status. Ehmann et al (2019) found that steam dried solid digestate from pig manure resulted in higher sunflower (Helianthus annuus L.) shoot and flower biomass than a mixture and calcium phosphates and struvite precipitated from the same digestate type.…”
Section: Use Of Solid Phase Digestate Products As Phosphorus-rich Pla...mentioning
confidence: 84%
“…In a crop rotation involving forage maize, potatoes (Solanum tuberosum L.), fodder beet (Beta vulgaris L.), and oats (Avena sativa L.), Vanden Nest et al (2015) found that application of solid phase digestate based on a mixture of organic waste, energy crops, and animal slurry increased soil calcium chloride-extractable phosphorus (P-CaCl 2 ) concentration and phosphorus leaching but not soil ammonium lactate-extractable phosphorus (P-AL) concentration, hot water-extractable phosphorus, or crop yield or quality compared with application of equal, higher, or lower doses of TSP to a soil with initially high phosphorus status. Bach et al (2022) found similar or higher maize biomass and biomass phosphorus content in treatments that received phosphorus as struvite, calcium phosphate, and magnesium phosphate precipitated from cow manure and maize silage-based digestate in combination with dried solid phase of the same types of digestate, than in treatments that received phosphorus as TSP on two soils with low phosphorus status. Ehmann et al (2019) found that steam dried solid digestate from pig manure resulted in higher sunflower (Helianthus annuus L.) shoot and flower biomass than a mixture and calcium phosphates and struvite precipitated from the same digestate type.…”
Section: Use Of Solid Phase Digestate Products As Phosphorus-rich Pla...mentioning
confidence: 84%
“…A study conducted in Karagwe found that low soil pH, ranging between 3.8 and 4.2 in agricultural fields, is one of the factors that limit agricultural yield [ 8 ]. According to a study by Bach et al [ 55 ], recycling materials from BS can solve low pH issues in soil when applied to acidic soils.…”
Section: Discussionmentioning
confidence: 99%
“…Farming practices generally adversely affect the AM relationship, and agricultural soil is depleted of AMF, especially in terms of the number of species [5,7]. Intensive agricultural production, for example, has resulted in the use of phosphorus (P) fertilizers that far exceed crop requirements, resulting in in the accumulation of overall and, in some instances, readily accessible P in the soil [8,9]. Consequently, crops have a reduced dependence on AM association and present lower root colonization and densities of settled propagules [10].…”
Section: Introductionmentioning
confidence: 99%